Analisis Implementasi Kebijakan E-Registration Dalam Meningkatkan Jumlah Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Pademangan Tahun 2021 - Amelia Nur Laili; Irawati Irawati (Jurnal Ilmu Administrasi Publik, 2023)
This study aims to determine and explain the implementation of e-registration policy in the Tax Office Pratama Jakarta Pademangan. The research method used is qualitative descriptive method, using data collection techniques through observation, interviews and documentation. The results of this study indicate that the implementation of e-registration policy can run well because the KPP always improve the quality of its services and has cooperated with other agencies. The obstacles faced are such as resources that are still standard, the system used is still often experiencing server down, there are still taxpayers who do not understand technology, do not understand how to operate the e-registration system and the choice of words used is still difficult to understand by taxpayers. Efforts that must be done is to improve the quality of the system to be better, conduct regular socialization to the public and prospective taxpayers both online and in person, expand cooperation with other agencies so that the information obtained by the public is clearer, and the use of wording in the e-registration system is further simplified in order to improve the quality.